Building waste caring character: School-based waste management training at SMP Muhammadiyah 10 Yogyakarta - Muhammad Muttaqien; Muhammad Arif Rizqi; Alifya Fathiyyah Nooresa; Dewi Ayu Indahsari; I Wayan Nain Febri (Universitas Muhammadiyah Magelang, 2024)
Since 2010, Muhammadiyah has recognized that waste materials such as plastic, paper, cans, and aluminum still contain energy. One of Muhammadiyah schools that utilizes plastic waste is SMP Muhammadiyah 10 Yogyakarta (Muhdasa) through its